2008
DOI: 10.1007/s00425-008-0844-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid alterations of gene expression and cytosine methylation in newly synthesized Brassica napus allopolyploids

Abstract: Allopolyploidy is an important speciation mechanism and is ubiquitous among plants. Brassica napus is a model system for studying the consequences of hybridization and polyploidization on allopolyploid genome. In this research, two sets of plant materials were used to investigate the transcriptomic and epigenetic changes in the early stages of allopolyploid formation. The first comparison was between a synthetic B. napus allotetraploid and its diploid progenitors, B. rapa (AA genome) and B. oleracea (CC genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
116
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 42 publications
11
116
0
1
Order By: Relevance
“…Both of these methods can distinguish between homoeologues, but are gel-based and therefore not fully quantitative in the measurement of expression levels. At the same time, anonymous surveys of many genes were carried out using cDNA amplified fragment length polymorphism gels in, for example, Brassica [30,31], Tragopogon [29], Triticum [32,33] and Arabidopsis [34].…”
Section: (B) Technological Issuesmentioning
confidence: 99%
“…Both of these methods can distinguish between homoeologues, but are gel-based and therefore not fully quantitative in the measurement of expression levels. At the same time, anonymous surveys of many genes were carried out using cDNA amplified fragment length polymorphism gels in, for example, Brassica [30,31], Tragopogon [29], Triticum [32,33] and Arabidopsis [34].…”
Section: (B) Technological Issuesmentioning
confidence: 99%
“…Recent studies using newly formed synthetic auto-or allopolyploid plants have shown that polyploidization is associated with genome-wide changes in gene expression, and these changes appear to be controlled primarily by epigenetic mechanisms such as cytosine methylation and small RNAs (Comai et al 2000;Kashkush et al 2002;Wang et al 2004;Xu et al 2009;Yu et al 2010).…”
mentioning
confidence: 99%
“…Further sequencing results of the methylation polymorphism fragments confirmed that most of the DNA methylation alteration happened at the repetitive sequences or non-coding sequences. However, the movement of transposable elements induced by DNA methylation alteration played an important role in the regulation of gene expression (Jin et al, 2008;Xu et al, 2009). The potential impacts, especially methylation alternation of transposable elements should be investigated on PD0111 and PD0113.…”
Section: Discussionmentioning
confidence: 99%